2010
DOI: 10.1103/physrevd.81.113002
|View full text |Cite
|
Sign up to set email alerts
|

BD*at zero recoil revisited

Abstract: We examine the B → D * form factor at zero recoil using a continuum QCD approach rooted in the heavy quark sum rules framework. A refined evaluation of the radiative corrections as well as the most recent estimates of higher order power terms together with more careful continuum calculation are included. An upper bound on the form factor of F(1) < ∼ 0.93 is derived, based on just the positivity of inelastic contributions. A model-independent estimate of the inelastic contributions shows they are quite signific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(83 citation statements)
references
References 19 publications
4
79
0
Order By: Relevance
“…By using zero recoil sum rules, the more recent form factor value obtained is [15,16] F (1) = 0.86 ± 0.02 (6) in good agreement with the lattice value in Eq. (4), but slightly lower in the central value.…”
Section: Heavy-to-heavy Decays Exclusive Decayssupporting
confidence: 64%
See 1 more Smart Citation
“…By using zero recoil sum rules, the more recent form factor value obtained is [15,16] F (1) = 0.86 ± 0.02 (6) in good agreement with the lattice value in Eq. (4), but slightly lower in the central value.…”
Section: Heavy-to-heavy Decays Exclusive Decayssupporting
confidence: 64%
“…The perturbative corrections to the coefficient of the matrix element of the kinetic operator have been evaluated at order α 2 s for generic observables, such as partial rates and moments [31,32]. Corrections at order α 2 s to the coefficient of the matrix element of the chromomagnetic [39,9,10] 39.54 ± 0.50 exp ± 0.74 th Rome (Lattice quenched ω = 1) [13,14] 37.4 ± 0.5 exp ± 0.8 th HFAG (Sum Rules) [15,16,39] 41.6 ± 0.6 exp ± 1.9 th…”
Section: Heavy-to-heavy Decays Exclusive Decaysmentioning
confidence: 99%
“…4 For some of the expectation values at order 1/m 4 b they can be estimated following the reasoning of Refs. [11,14]. The nonfactorizable contributions taken at face value appear to be about 50% of the ground-state one [15].…”
Section: Summary For O(λmentioning
confidence: 99%
“…In [8] the parameters associated with O(1/m 4,5 Q ) effects have been estimated in the ground state saturation approximation, finding a relatively small +0.4% net effect on |V cb |. Recently, the validity of the ground state saturation has been investigated [9], and it has been shown that the non-factorizable contributions can be in general comparable to the factorizable ones. Additional work is therefore necessary to assess the importance of higher order power effects.…”
Section: Introductionmentioning
confidence: 99%
“…i are related to real gluon emission and are given by 9) with z =û + ρ. Of course, the functions R (π) i are regular in the limitû → 0.…”
Section: The Functions R (π)mentioning
confidence: 99%